Análise das manifestações patológicas em estruturas de concreto armado - Estudo de caso: Macapá Hotel - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2024)
Old structures, considered cultural heritage and postcards, are common in various cities around the world. Many of these constructions, now disused or abandoned, are susceptible to pathological manifestations that can compromise their performance, durability, and visual comfort. This study focuses on the Macapá Hotel, a historic building constructed in the 1940s and expanded in 1982, which has been abandoned for the past four years, suffering from lack of maintenance and the consequent appearance of pathologies. The objective of the study is to analyze this historic building, identify the present anomalies, and discuss their possible causes, also addressing the risk level and proposing solutions for treating these pathological manifestations. To this end, the methodology includes a descriptive research with a bibliographic review for theoretical foundation and reader adaptation to the results, as well as field surveys that will allow visual inspection and the realization of non-destructive tests, such as Sclerometry. The concepts and classifications will follow the IBAPE (2012) building inspection standard, which serves as a basis for the building inspection, inspection level, and risk assessment presented in this work. The results will be discussed mainly based on the dissertation by Carballal Junior (2019), which addresses the most common pathological manifestations in buildings over five years old, coinciding with those observed at the Macapá Hotel, such as corrosion and exposure of reinforcements, concrete segregation, and moisture problems. The data will be organized in tables for easier reading, in addition to presenting the results of non-destructive tests, which indicate elements with good compressive strength, all above 20 MPa, although some elements have a pH below the desired level.
Keywords: Conservação de edifícios; Edificação histórica; Avaliação de risco estrutural; Esclerometria; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS::ESTRUTURAS DE CONCRETO